2021
DOI: 10.1002/mde.3499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of retailers' free shipping promotions on manufacturers' product sales and product review ratings in multichannel retailing

Abstract: It is substantial for manufacturers to know the optimal market structure in terms of retailers using free shipping promotions that help them decide whether and how to subsidize retailers. Our research uses fixed‐effect models to empirically examine the impact of the proportion of free shipping retailers on consumer purchase decision and perceived product quality with secondary data from http://Amazon.com. We find that more retailers using free shipping decrease a manufacturer's product sales while increasing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…This variable is calculated as the average number of other products sold by the retailers in the market within the category (Li & Wang, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This variable is calculated as the average number of other products sold by the retailers in the market within the category (Li & Wang, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, prior research revealed that trust leads to preference (Chinomona et al, 2013) and consumers would buy more units from their preferred retailers (Bucklin et al, 1998). Furthermore, trust in the retailer can lower potential consumers' risk perceptions and induce them to switch from other substitutes (Li & Wang, 2021).…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Wu et al ( 2021 ) focused on the relative effects of coupons vs. free shipping on review ratings for an e-commerce website. Li and Wang ( 2021 ), using reviews from Amazon, found that more retailers using free shipping increased product review ratings.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The profit rates of Tmall.com reach 5-15 % increases per year by adopting different selling modes 2 . Similarly, at Amazon.com, another leading online retail platform, over 60% of the firms have adopted the bundling mode, which contributed to 55% of the revenue generated in 2021 [20]. As the demand for this selling model continues to escalate, platforms have built their own strategies to optimize profitability when bundling is feasible, requiring the development of corresponding pricing strategies [10,34].…”
mentioning
confidence: 99%